Automotive mechanics - Crouse, William Harry; Anglin, Donald L. (McMillan/McGraw-Hill, 1993)
This edition of the text covers the latest developments in automotive design, construction, operation, diagnosis, and service. The text integrates the new with the old, simplifying explanations, shortening sentences, and improving readability. Hundreds of illustrations cover new developments, especially those relating to the foreign automotive industry and federal laws governing automotive air pollution, safety, and fuel economy. The Tenth Edition contains two four-color illustrated sections. Many chapters end with vocabulary words and "think-type" review questions, in addition to the National Institute of Automotive Service Excellence (ASE) style of multiple-choice questions. For schools seeking program certification by the national Automotive Technicians Education Foundation (NATEF), the high-priority items from their diagnosis, service, and repair task lists have been included.